Global research landscape of HIV and Kaposi’s sarcoma: a visualized bibliometric analysis - Ma, Shengwei; Chen, Xuannan; Lai, Yu (Frontiers in Microbiology, 2025)
BackgroundHuman immunodeficiency virus (HIV) infection remains a significant global health challenge, with Kaposi’s sarcoma (KS) being one of the most common AIDS-defining cancers. This study aimed to investigate the development of HIV and KS (HIV-KS) research through bibliometric analysis and to assess the current literature to advance the field.MethodsWe gathered 1,568 publications on HIV-KS from the Web of Science Core Collection and analyzed them to visualize the data, identifying future directions and emerging trends by CiteSpace software. Betweenness centrality, count, and burst value were used as metrics.ResultsThe number of publications on HIV-KS fluctuated in the included literature. The most important contributions from countries and institutions were the United States and the National Institutes of Health (NIH) – USA, respectively. Denise Whitby was the most prolific author, while Yuan Chang had the highest cocitation count. The most commonly cited article is “Kaposi sarcoma (2019).” The hotspots in this field are “basic mechanism,” “Kaposi’s sarcoma-associated herpesvirus-related disease,” and “treatment measures.” The present research direction of HIV-KS is focused on exploring the emerging prevalence, diagnostic methods, and therapeutics.ConclusionThis study outlines the current landscape and emerging hotspots of HIV-KS research, offering insights into thematic evolution and collaboration patterns. By identifying key research priorities and structural gaps, the findings can inform future scientific directions, guide resource allocation, and support more context-sensitive strategies for the diagnosis, treatment, and prevention of HIV-KS.